On ensuring economic security enterprises in market conditions - Berezhnova Elena; Dzholdosheva Tamara; Abykeeva Meerim; Bozieva Zuhra; Niyazbekova Shakizada; Kunskiy Andrey; Varzin Vasiliy (BIO Web of Conferences)
The article considers the provision of economic security, which belongs to the category of security economics and is an important branch of security science. The economic security of an enterprise begins from the point of view of economic analysis and decision–making. The article analyzes the stakeholders of the economic security of the enterprise, and conducts a more systematic discussion. Today, issues such as enterprise risk analysis, how to plan projects to improve and ensure safety, how to assess the true losses from accidents, how to make decisions in this area, how to conduct inspections and establish a long–term safety mechanism are more relevant than ever. The authors have identified factors affecting the economic security of enterprises in the country. Recommendations are presented on how organizations can cope with various economic threats and risks, maintain the stability of their financial position, and ensure sustainable functioning and development in the face of changes and uncertainty in the market. An integrated approach with innovative elements for solving problems and challenges is proposed.